Analysis of the Effectiveness of Using Augmented Reality (AR) on Science Learning in Elementary Schools: A Systematic Literature Review - Rohmani Rohmani; Fathia Azzahra; Novi Ayu Kristiana Dewi (Journal of Psychology and Instruction, 2024)
The use of Augmented Reality (AR) in science learning in primary schools enriches students' learning experience by presenting interactive and visual content, allowing them to explore scientific concepts directly through advanced technology. The objective of this study is to scrutinize the effectiveness of using Augmented Reality (AR) on science learning in elementary schools through a systematic review. The study employs a Systematic Literature Review (SLR) as its methodology by going through 4 stages, and the articles analyzed in this study were released in 2019-2023 in the Scopus database. In stage 1 or the identification stage, 27,520 documents were obtained with the keyword “Augmented Reality” and year restrictions ranging from 2019 to 2023. Then in stage 2 or the filtering stage added the keyword “Science” which obtained 1,874 documents and added back the keyword “Elementary School” so as to obtain the results of 51 documents. Furthermore, at stage 3 or eligibility, the documents that have been obtained are selected again according to the eligibility criteria, namely documents with citations above 10 and can be accessed or downloaded, resulting in 8 documents. According to the study's outcomes, it is evident that utilizing Augmented Reality (AR) is an effective method for enhancing science education in elementary school settings.